Contributions of the snake venoms of Bothrops asper, Crotalus simus and Lachesis stenophrys to the paraspecificity of the Central American polyspecific antivenom (PoliVal-ICP). (15th March 2018) - Solano, Gabriela; Gómez, Aarón; Corrales, Greivin; Chacón, Danilo; Estrada, Ricardo; León, Guillermo
Abstract: PoliVal-ICP antivenom is produced from plasma of horses immunized toward the venoms of Bothrops asper, Crotalus simus and Lachesis stenophrys . The antibody response induced by these venoms confers PoliVal-ICP the capacity to neutralize the venoms of the most important Central American viperids, including not only homologous venoms (i.e., venoms used as immunogen), but many heterologous venoms (i.e., venoms not used as immunogen). In this work, the individual contributions of homologous venoms to the paraspecificity of PoliVal-ICP were inferred from the capacity of experimental monospecific antivenoms toward venoms of B. asper (anti-Ba), C. simus (anti-Cs) and L. stenophrys (anti-Ls), and an experimental polyspecific antivenom (anti-Ba/Cs/Ls) to neutralize the lethality induced by different venoms in mice. It was found that all antivenoms neutralized their corresponding homologous venoms. Moreover, the anti-Ba antivenom cross-neutralized the venoms of Agkistrodon howardgloydi, Atropoides picadoi, Bothriechis lateralis, Bothriechis supraciliaris and Porthidium ophryomegas ; the anti-Cs antivenom cross-neutralized the venoms of B. lateralis, B. supraciliaris, Cerrophidion sasai and Porthidium nasutum ; and the anti-Ls antivenom cross-neutralized the venoms of B. lateralis, B. supraciliaris, C. sasai and Lachesis melanocephala . All venoms neutralized by any monospecific antivenom were also neutralized by the anti-Ba/Cs/Ls antivenom. Venoms of Atropoides mexicanus, Bothriechis nigroviridis and Bothriechis schlegelii were not neutralized by any experimental antivenom, thus explaining the limitations of PoliVal-ICP to neutralize these venoms. Consequently, an enlargement of the neutralization scope of PoliVal-ICP could be achieved by including these venoms in the group of those used as immunogens. Highlights: Venoms of the snakes B. asper, C. simus and L. stenophrys are used to produce the antivenom PoliVal-ICP. PoliVal-ICP neutralizes venoms of the most important Central American snakes, including many heterologous venoms. Origin of the paraspecificity of PoliVal-ICP was inferred from the neutralizing capacity of experimental antivenoms. Elucidating why/how antivenom paraspecificity occurs is fundamental to improve PoliVal-ICP performance.